Proteomic characterization of outer membrane vesicles from gut mucosa-derived fusobacterium nucleatum - Liu, Jinjing; Hsieh, Ching-Lin; Gelincik, Ozkan; Devolder, Bryan; Sei, Shizuko; Zhang, Sheng; Lipkin, Steven M.; Chang, Yung-Fu (Journal of proteomics, 2019)
Fusobacterium nucleatum is a Gram-negative bacterium commonly found in the oral cavity and is often involved in periodontal diseases. Recent studies have shown increased F. nucleatum prevalence in colorectal cancer (CRC) tissues, and causal data has linked this bacterium to CRC tumorigenesis. Immune-based approaches to contain, reduce or eradicate its gut colonization may prevent CRC. Outer membrane vesicles (OMVs) are naturally produced by Gram-negative bacteria, typically contain multiple putative virulence factors and may elicit protective immune responses if used as vaccines. Here, OMVs were isolated from F. nucleatum cultures and purified using gradient centrifugation. Proteins contained within the OMVs were identified by nano LC/MS/MS analysis. Of 98 proteins consistently identified from duplicate analyses, 60 were predicted to localize to the outer membrane or periplasm via signal peptide driven translocation. Of these, six autotransporter proteins, which constitute the majority of protein mass of OMVs, were associated with Type V secretion system. In addition, other putative virulence factor proteins with functional domains, including FadA, MORN2 and YadA-like domain, were identified with multiple exposed epitope sites as determined by in silico analysis. Altogether, the non-replicative OMVs of F. nucleatum contain multiple antigenic virulence factors that may play important roles in the design and development of vaccines against F. nucleatum. Fusobacterium nulceatum has been proved playing significant role in colorectal carcinogenesis. Outer membrane vesicles are nanoparticles that naturally secreted by Gram-negative bacterial containing various antigenic components, which provides new insight in vaccine development. Understanding the constituents of F. nucleatum OMVs will provide fundamental information and potential strategies for OMV-based F. nucleatum vaccines design. Based on our knowledge this is the first proteomic study of OMVs from F. nucleatum. [Display omitted] •98 proteins were consistently identified from F. nucleatum outer membrane vesicles.•Autotransporter proteins were the main components.•Putative virulence factors such FadA, MORN2 and YadA were also identified.•Nano-size and numerous exposed epitopes make OMV ideal for vaccine design.